The Pomace Extract Taurisolo Protects Rat Brain From Ischemia-Reperfusion Injury - Lapi, Dominga; Stornaiuolo, Mariano; Sabatino, Lina; Sommella, Eduardo; Tenore, Giancarlo; Daglia, Maria; Scuri, Rossana; Di Maro, Martina; Colantuoni, Antonio; Novellino, Ettore (Frontiers in Cellular Neuroscience, 2020)
Taurisolo® is a pomace extract from Aglianico Grapes, a wine cultivar native to Campania (Southern Italy). It exhibits a very high polyphenolic content and, consumed as nutraceutical, is effective in reducing the level of Trimethylamine N-oxide (TMAO), a cardiovascular diseases risk factor marker. We here show the effects of Taurisolo® on rat brain microvascular alterations induced by diminution in cerebral blood flow (CBFD) for 30 min, due to bilateral common carotid artery occlusion, and subsequent blood flow restoration (CBFR) for 60 min. The rat pial microcirculation was investigated by intravital fluorescence microscopy through a parietal closed window implanted into the skull bone. The rat pial arterioles were classified according to Strahler’s ordering scheme, from smaller penetrating arterioles up to the larger ones. Western blotting analysis and mass spectrometry-based metabolomics were used to investigate the expression of endothelial nitric oxide synthase (eNOS) or the presence of peroxidated cardiolipin and several inflammatory mediators, respectively. Radical Oxygen Species (ROS) formation and neuronal loss were assessed. In rats CBFD and CBFR caused decrease in arteriolar diameter, increase in fluorescent leakage and in adhesion of leukocytes to venular walls, reduction in the length of perfused capillaries and increment of ROS formation with large infarct size. Taurisolo®, intravenously or orally administered, induced pial arteriolar dilation (up to >30% of baseline), prevented fluorescent leakage, adhesion of leukocytes, ROS formation, while facilitated capillary perfusion and significantly reduced infarct size. These effects were accompanied by increase in eNOS expression. Mass-spectrometry metabolomics analysis detected a marked decrease in the amount of peroxidated cardiolipin and pronounced reduction in pro-inflammatory prostaglandins and tromboxane TxB2. All together, these results extend the nutraceutical potential of Taurisolo® and suggest its eligibility for preventing brain damage due to ischemia-reperfusion injury.